PENYULUHAN PRAKTIK KELOMPOK TANI DALAM PENGOLAHAN BAHAN BAKU BIO-PLASTIK DENGAN MEMANFAAFKAN LIMBAH KULIT KOPI - Berlianti, Nindha Ayu; Supriyanto, Edy; Rokhmah, Dewi (Universitas Mataram, 2024)
Pace Village is one of the largest coffee producers in Jember Regency. The majority of the population of Pace village are coffee farmers who are members of a combined farmer group consisting of 10 farmer groups with each group having approximately 10-20 farmers. During the coffee harvest season, the remaining coffee husk waste products are still not utilized optimally, generally the remaining coffee farming products are sold at a very cheap price, namely around 8 thousand per/large bag. This is our main reason as a service team to provide added value to coffee skin waste by providing training and practice in improving the skills of coffee farmers in managing and processing coffee skin waste. The activity began with a request from partners to provide counseling, practice and assistance in managing and processing post-harvest coffee skin waste. Participation in service activities involves an active coffee farming community of 50 farmers. The result of this activity is that Gapoktan members have knowledge and skills in managing and processing coffee husk waste into raw material for coffee husk flour which can later be further characterized into bio plastic, bio pellets, animal feed mixture, block compost, cascara peat, bio pop, bio briquettes and other processed products that have added value so that they can provide additional income, especially for coffee farmers in Pace village, Silo sub-district, Jember district. Through the community service activities carried out, the hope is to increase the skills and income of partners in managing and processing coffee skin waste into raw material for coffee skin flour.